Sistem Informasi Pengelolaan Kearsipan Berbasis Web Kelurahan Mulyasari - Kadek Dwi Riska Santi; A. Ferico Octaviansyah Pasaribu (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2023)
At present the filing process in Mulyasari Village is still being done manually so that it experiences problems in its management, such as letters being tucked away and difficult to find when needed. In addition, mail archives will also take up space if it continues to be done manually, so an information system is needed that can help alleviate this. In carrying out its duties, this office is involved in a lot of correspondence. About 4 to 7 incoming letters are received in a month, while 15 to 10 outgoing letters. The purpose of this research is to develop a website-based archive management information system that can assist in managing electronic records better. The design of an archive system to help manage incoming and outgoing letters in Mulyasari sub-district using the prototype method. System testing is carried out using the ISO 25010 testing method covering 2 (two) main characteristics of ISO 25010, namely Functional Suitablity and Usability. System design uses UML (Unified Modeling Language) with each diagram, namely use case diagrams, activity diagrams and class diagrams. From the calculations performed using the Likert Scale, the results obtained were 89%. So it can be concluded that the design of this system is stated to be very good to use and feasible to implement.